Engineered thermostable fungal cellulases exhibit efficient synergistic cellulose hydrolysis at elevated temperatures. Issue 12 (5th August 2014) - Trudeau, Devin L.; Lee, Toni M.; Arnold, Frances H.
ABSTRACT A major obstacle to using widely available and low‐cost lignocellulosic feedstocks to produce renewable fuels and chemicals is the high cost and low efficiency of the enzyme mixtures used to hydrolyze cellulose to fermentable sugars. One possible solution entails engineering current cellulases to function efficiently at elevated temperatures in order to boost reaction rates and exploit several other advantages of a higher temperature process. Here, we describe the creation of the most stable reported fungal endoglucanase, a derivative of Hypocrea jecorina (anamorph Trichoderma reesei) Cel5A, by combining stabilizing mutations identified using consensus design, chimera studies, and structure‐based computational methods. The engineered endoglucanase has an optimal temperature that is 17°C higher than wild type H. jecorina Cel5A, and hydrolyzes 1.5 times as much cellulose over 60 h at its optimum temperature compared to the wild type enzyme at its optimal temperature. This enzyme complements previously engineered highly active, thermostable variants of the fungal cellobiohydrolases Cel6A and Cel7A in a thermostable cellulase mixture that hydrolyzes cellulose synergistically at an optimum temperature of 70°C over 60 h.The thermostable mixture produces three times as much total sugar as the best mixture of the wild type enzymes operating at its optimum temperature of 60°C, clearly demonstrating the advantage of higher temperature cellulose hydrolysis. Biotechnol. Bioeng. 2014;111: 2390–2397. © 2014 Wiley Periodicals, Inc.